Laporan kasus: manajemen anestesi pada pasien hipospadia - Yosi Ajeng Sabila (SEHATI: Jurnal Kesehatan, 2022)
abnormal development of the urethral fold and the ventral foreskin of the penis that causes abnormal positioning of the urethral opening. Patients diagnosed with hypospadias should be referred for surgical evaluation within the first weeks of life. If parents want circumcisions for their newborns, the presence of any penile abnormality should contraindicate the procedure, given that the foreskin is used in the arthroplasties. Surgical correction is the mainstay treatment of proximal hypospadias. In proximal penile, penoscrotal, and scrotal hypospadias with chordee, the patient commonly undergoesÂ a two-stage repair with initial surgery consisting of urethroplasty and penile straightening with subsequent urethral plate tabularization. A 13 years ago the patient came to the Pediatric Surgery with a complaint that the bladder hole was under the genitals. This has been known by the patient's family since birth, but they do not want to take the patient to see a doctor because they are worried. A right surgery should minimize the discomfort felt by the patient. Therefore, it is necessary to prepare an anesthetic plan and appropriate preoperative, intraoperative and postoperative management to avoid complications that may occur.